(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Abstract. The article considers the need to introduce the latest computer technologies into the educational process to contribute to the formation and provision of professional competencies of applicants of education studying the specialty “Accounting and Taxation.” Modern information technologies used in the educational space are considered an essential factor in the interaction between teacher and students. Distance education flexibility, i.e., the ability to study individually, choosing the time, place, and tempo of learning, are precisely the advantages, which are considered while organizing the educational process. The task of academic staff is to provide the students with maximum opportunities to remotely process the proposed material and perform all control exercises conveniently in compliance with the requirements for specific tasks. Distance education can be used as the main form of education for preparing students of the second level of education studying at the specialty “Accounting and Taxation”. To investigate the information support of professional competencies of applicants of education studying at “Accounting and Taxation”, we analyzed the practical experience of bachelors and masters studying the following accounting disciplines at Lesya Ukrainka Volyn National University with the use of distance education methods: “Managerial Accounting”, “Forensic accounting expertise”, “Accounting in foreign countries”, “Accounting and Taxation of international transactions”, “Accounting in enterprise management”, “Applied econometrics”, “International standards of accounting and financial reporting”, “Financial reporting consolidation”. The educational material allocation and access to it took place using standard software tools. The type of courses and features of the work organization depends on the format of a course chosen at its creation and adjustment stage. During the development of distance learning courses in the modern educational space, more attention is paid to the information environment service – “Moodle”.